Robust Design of Wideband Loudspeaker Arrays - Tashev, Ivan; Droppo, Jasha; Seltzer, Mike; Acero, Alex (Proc. of International Conference on Audio, Speech and Signal Processing, 2008)
Loudspeaker arrays usually are used in professional sound reinforcement systems to provide uniform sound coverage of the listening area. They can also be used for focusing the sound to the user for semi-private communication and reducing the overall noise pollution. In this paper we describe a procedure for designing broadband beamformers for loudspeaker arrays that is robust to the manufacturing tolerances of the loudspeakers – the limiting factor for achieving high directivity. The designed beamformer is evaluated using simulations and measurements of actual loudspeaker array.